Time evolution of stimulated Raman scattering and two-plasmon decay at laser intensities relevant for shock ignition in a hot plasma. (2019) - Cristoforetti, G.; Antonelli, L.; Mancelli, D.; Atzeni, S.; Baffigi, F.; Barbato, F.; Batani, D.; Boutoux, G.; D'Amato, F.; Dostal, J.; Dudzak, R.; Filippov, E.; et al.
Abstract : Laser–plasma interaction (LPI) at intensities $10^{15}{-}10^{16}~\text{W}· \text{cm}^{-2}$ is dominated by parametric instabilities which can be responsible for a significant amount of non-collisional absorption and generate large fluxes of high-energy nonthermal electrons. Such a regime is of paramount importance for inertial confinement fusion (ICF) and in particular for the shock ignition scheme. In this paper we report on an experiment carried out at the Prague Asterix Laser System (PALS) facility to investigate the extent and time history of stimulated Raman scattering (SRS) and two-plasmon decay (TPD) instabilities, driven by the interaction of an infrared laser pulse at an intensity ${\sim}1.2× 10^{16}~\text{W}· \text{cm}^{-2}$ with a ${\sim}100~\unicode[STIX]{x03BC}\text{m}$ scalelength plasma produced from irradiation of a flat plastic target. The laser pulse duration (300 ps) and the high value of plasma temperature ( ${\sim}4~\text{keV}$ ) expected from hydrodynamic simulations make these results interesting for a deeper understanding of LPI in shock ignition conditions. Experimental results show that absolute TPD/SRS, driven at a quarter of the critical density, and convective SRS, driven at lower plasma densities, are well separated in time, with absolute instabilities driven at early times of interaction and convective backward SRS emerging at the laser peak and persisting all over the tail of the pulse. Side-scattering SRS, driven at low plasma densities, is also clearly observed. Experimental results are compared to fully kinetic large-scale, two-dimensional simulations. Particle-in-cell results, beyond reproducing the framework delineated by the experimental measurements, reveal the importance of filamentation instability in ruling the onset of SRS and stimulated Brillouin scattering instabilities and confirm the crucial role of collisionless absorption in the LPI energy balance.